Fermented chickpea (Cicer arietinum L.) as a functional food: Meatless “vegan” burgers - R. M. Mohamed; M. R. Ali (Пищевые системы)
The global desire for ethical, sustainable, and nutritional food choices has intensified interest in plant-based meat alternatives. Researchers and food manufacturers have prioritized the development of superior alternatives to meat and dairy products due to the increasing popularity of vegetarian and vegan diets among consumers. Chickpeas, a leguminous source abundant in protein and fiber, and mushrooms are rich in umami chemicals and can potentially be essential ingredients in plant-based meat products. Plant-based foods’ nutritional profile and sensory attributes can be improved through fermentation, a conventional method frequently employed in food production. This process can increase the allure of these foods to consumers. Therefore, this research aims to create a new product from plant sources that substitutes for meat products. The chickpea was fermented by Aspergillus oryzae (AUMC B2) for different fermentation periods (7, 10, and 14 days) to determine the optimum fermentation time to enhance the umami taste (meat flavor). Chickpeas and mushrooms were the primary raw materials for plant-based burgers. Fermented chickpeas were used to prepare vegan burgers at different fermentation times (7 days: FC7, 10 days: FC10, and 14 days: FC14). The sensory attributes of vegan burgers were compared to those of the nonfermented control sample. The results showed that the samples of FC10 meatless burgers recorded the highest score of taste and odor compared to the control. Based on these results, a chemical analysis was conducted for the meatless product FC10 and its control. The findings showed that the fermentation process increased the protein content and decreased the content of fats and carbohydrates in the fermented meatless burger.